A forgotten helmet from Silniczka in Poland - Mariusz R. Rychter; Piotr Strzyż (Fasciculi Archaeologiae Historicae, 2016)
The paper discusses a well-preserved helmet discovered in the vicinity of an Early Medieval cemetery in Silniczka near Radomsko. The helmet was made from two pieces of metal sheet, which were riveted together. In its upper part the presence of copper and gold sheets was noticed. The helmet can be dated to the 11th-first half of the 12th c. and it belongs to unique finds from the territory of Poland